HUBUGAN PAPARAN DEBU KAPAS DAN KARAKTERISTIK INDIVIDU DENGAN GEJALA PENYAKIT BISINOSIS PADA PEKERJA SPINNING 1 PT. X KABUPATEN SEMARANG - Robby Aditya Saputra; Ari Suwondo; Siswi Jayanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Cotton dust is a factor of air pollutants that cause disease byssinosis. In addition to cotton dust exposure byssinosis disease is also influenced by the characteristics of the individual. Based on the preliminary results of the survey 70% of workers in the spinning mills 1 PT. X has a cough, shortness of breath and respiratory symptoms suspected byssinosis disease. The purpose of this study was to analyze the relationship between exposure to cotton dust and characteristics of individuals with symptoms of the disease byssinosis on workers in the spinning 1 PT. X Semarang Regency. This type of research is observational analytic cross-sectional study design. The variables measured were cotton dust levels, age, gender, length of employment, nutritional status, use of masks, smoking, history of pulmonary disease and lung vital capacity. Determination of the sample using simple random sampling technique was followed by a minimum sampling techniques to obtain a total sample of 53 people. Univariate analysis showed that the prevalence of disease symptoms byssinosis by 62.3%. Statistical test results by using test Spearman rank correlation showed no relationship between levels of cotton dust with disease symptoms byssinosis (p = 0.019), tenure with the symptoms of the disease byssinosis (p = 0.001), As for the variables of sex, age, nutritional status, the use of masks, smoking, and a history of pulmonary disease there was no correlation with disease symptoms byssinosis. Suggestions in this research is to rotate the work to the worker who has symptoms byssinosis and has worked for over 5 years to the section that has a low dust content value.